Global trends and regional differences in the burden of cancer attributable to secondhand smoke in 204 countries and territories, 1990–2019 - Maimaitiming, Mailikezhati; Wang, Minmin; Luo, Yanan; Wang, Jia; Jin, Yinzi; Zheng, Zhi-Jie (Frontiers in Oncology, 2022)
Background To describe the status quo and trends in the global burden of all cancers caused by secondhand smoke during 1990–2019. Methods Data on cancer associated with secondhand smoke were extracted from the Global Heath Data Exchange. Cancer burden was measured by cancer-related deaths, disability-adjusted life years (DALYs), years lived with disability (YLDs), and years of life lost (YLLs). Results In 2019, age-standardized rates of death, DALYs and YLLs among the cancer population globally caused by secondhand smoke were 1.60, 38.54 and 37.77, respectively. The proportions of these in the total cancer burden for all risk factors combined decreased slightly from 1990 to 2003 and then increased from 2004 to 2019. In 2019, >50% of the cancer burden was concentrated in men aged 55–75 years and women aged 50–70 years. Between 1990 and 2019, there was an increase in age-standardized rates of death, DALYs, YLDs and YLLs among those aged ≥70 years. The age-standardized YLDs rate attributable to secondhand smoke was higher among women; it decreased in men but increased in women, causing a wider gap between the sexes. A greater cancer burden was mainly seen in North America in 1990 and Europe in 2019. Reductions in the annual rate change of cancer burden were found mainly in North America and Oceania, while increases were found in Africa and Asia. In 2019, high–middle- and middle-SDI countries had higher age-standardized rates of deaths, DALYs, YLDs and YLLs than the global level. During 1990 and 2019, the largest decline in cancer burden was seen in high-SDI countries, while middle- or low-SDI countries experienced increases in all age-standardized rates. Conclusions Cancer burden attributable to secondhand smoke is concerning given the increasing health loss and differences in distribution of cancer burden worldwide. Further studies are needed to investigate the causes of disparities in cancer burden attributable to secondhand smoke and to improve understanding of the contribution of secondhand smoke to the burden of different types of cancer.